A case of natural conception after uterine artery embolization - Dharmarha, Noor; Hajari, Anju; Konda, Anuradha; Reddy, Venkatesa Muni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Our objective of this case report is to highlight the value of uterine artery embolization as a means of conservative management of uterine arteriovenous malformation in patients wanting preservation of fertility. A 24 years old woman, P1L1A2 presented with complaints of heavy menstrual bleeding for two months. She had a previous term caesarean section in 2014, followed by curettage twice, in 2016 and 2017. The first episode of heavy bleeding occurred two months after the last curettage. Previous menstrual cycles were regular with moderate flow. The patient was started on combined oral contraceptive pills but she did not respond to medical treatment. Transvaginal scan and Doppler showed uterine AVM and endometrial thickness of 7.7mm. Beta hCG was less than 1.2. Digital subtraction angiography and bilateral uterine artery embolization was done. Patient conceived spontaneously a year after the procedure and delivered a healthy baby at term by elective caesarean section. Angiography and uterine artery embolization has revolutionized the management of AVM and contrary to popular belief, the pregnancy outcome after UAE was good.